The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.psj.2020.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Citrullus lanatus essential oils inclusion in diets elicit nutraceutical effects on egg production, egg quality, and physiological characteristics in layer hens

Abstract: The study evaluated the effects of Citrullus lanatus essential oils inclusion in diet on egg production, egg quality, and physiological parameters in layer hens. A total of 72 White Leghorn point-of-lay hens at 18 wk were used for the study. The hens were randomly allocated to following 3 dietary treatments: 1) commercial layer diet (control), 2) commercial diet + 1 g C. lanatus essential oil/kg feed ( 1gCL ), and 3) commercial diet + 2 g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
1
10
0
1
Order By: Relevance
“…These results may be ascribed to the positive effect of prolonging photoperiod on serum reproductive hormone level and ovarian follicle development ( Cui et al., 2019a ). Besides, the higher ADFI was always associated with more egg mass ( Marume et al., 2020 ), which was also verified by our result that consistent increases were observed in egg mass and ADFI, accompanied with no change in feed conversion ratio. The higher ADFI driving by appropriate photoperiod ( Schwean-Lardner et al., 2012 ) may be owing to the combination of better mobility and longer feeding ( Schwean-Lardner et al., 2013 , 2014 ; Cui et al., 2019b ).…”
Section: Discussionsupporting
confidence: 88%
“…These results may be ascribed to the positive effect of prolonging photoperiod on serum reproductive hormone level and ovarian follicle development ( Cui et al., 2019a ). Besides, the higher ADFI was always associated with more egg mass ( Marume et al., 2020 ), which was also verified by our result that consistent increases were observed in egg mass and ADFI, accompanied with no change in feed conversion ratio. The higher ADFI driving by appropriate photoperiod ( Schwean-Lardner et al., 2012 ) may be owing to the combination of better mobility and longer feeding ( Schwean-Lardner et al., 2013 , 2014 ; Cui et al., 2019b ).…”
Section: Discussionsupporting
confidence: 88%
“…Dietary supplementation of EOs containing menthol, anethol and eugenol [ 39 ] as well as carvacrol alone [ 40 ], or combined with either thymol [ 41 , 42 , 43 ] or thymol and limonene [ 44 ] has been shown to promote growth performance of broiler chickens. Similar positive effects on production performance were obtained by supplementing laying hens diets with thymol and cinnamaldehyde [ 39 ], star anise oil [ 45 ], Citrullus lanatus EO [ 46 ], tea tree EO [ 47 ] and peppermint oil [ 48 ]. Several other studies have also evaluated the effects of supplementing black cumin ( Nigella sativa L.) seeds on broilers, quails and laying hens.…”
Section: Effects Of Phytogenic Feed Additives On Chickensmentioning
confidence: 85%
“…The changes in size and structure of internal organs are important for predicting the effect of diet and its components on the development and function of organs in laying hens. Generally, as the size of the organ increases, the energy required to maintain the organ increases, which in turn decreases the amount of energy input to productivity [ 4 ]. Our results revealed that dietary SPA supplementation did not affect relative weights of internal organs (liver, spleen, heart, gizzard, jejunum, and cecum), intestinal length, intestine pH, and abdominal fat, which indicated that dietary supplementation with SPA up to 3 g/kg of diet could have no observed adverse effects on organ development.…”
Section: Discussionmentioning
confidence: 99%